2020
DOI: 10.1016/j.cmi.2019.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Cefepime neurotoxicity: thresholds and risk factors. A retrospective cohort study

Abstract: Objectives: Toxic serum cefepime trough concentrations are not well defined in the current literature. We aimed to define a more precise plasma trough concentration threshold for this antibiotic's neurological toxicity and to identify individuals at risk for developing neurotoxic side effects. Methods: Retrospective study including all individuals who underwent cefepime therapeutic drug monitoring (TDM) between 2013 and 2017. Individuals with cefepime concentrations other than trough were excluded. The primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(108 citation statements)
references
References 24 publications
(27 reference statements)
3
100
1
4
Order By: Relevance
“…Although trough concentrations have primarily been studied, peak concentrations and AUC have also been investigated as potential parameters for neurotoxicity. Overall, the data are limited, and a definitive threshold for toxicity has not been defined . Empiric dose reduction due to concern for causing neurotoxicity is a consideration; however, lower doses may result in failure to attain the pharmacodynamic target and expose the patient to risk of treatment failure or bacterial resistance .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although trough concentrations have primarily been studied, peak concentrations and AUC have also been investigated as potential parameters for neurotoxicity. Overall, the data are limited, and a definitive threshold for toxicity has not been defined . Empiric dose reduction due to concern for causing neurotoxicity is a consideration; however, lower doses may result in failure to attain the pharmacodynamic target and expose the patient to risk of treatment failure or bacterial resistance .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the data are limited, and a definitive threshold for toxicity has not been defined. [41][42][43][44][45] Empiric dose reduction due to concern for causing neurotoxicity is a consideration; however, lower doses may result in failure to attain the pharmacodynamic target and expose the patient to risk of treatment failure or bacterial resistance. 8,46 Our results support the use of EI cefepime in patients receiving CRRT to optimize pharmacodynamic target attainment in critically ill patients who are at risk for resistant organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic drug monitoring (TDM) studies show that the incidence of CIN has increased, from 11% to 23.2% [26][27][28]. In the French pharmacovigilance database on serious CNS adverse effects, cefepime was the most common drug among cephalosporins to be associated with CNS adverse effects [29].…”
Section: Incidencementioning
confidence: 99%
“…Some investigators measured serum cefepime concentrations and demonstrated the association between serum cefepime concentrations and the occurrence of CIN [28,45,51]. Others described that clinical improvement of CIN was associated with a decrease in the blood concentration of cefepime [2,26,45,46].…”
Section: Serum Cefepime Concentrationmentioning
confidence: 99%
“…A recent retrospective study conducted by Boschung-Pasquier et al assessed serum cefepime trough concentrations in 319 adult patients. 18 Cefepime serum trough concentrations were measured to determine correlation with neurotoxicity. Probability of neurotoxicity was determined to be 25% in patients with trough concentrations !12 mg/L and 50% in patients with trough concentrations !16 mg/L, with 100% of patients exhibiting signs of neurotoxicity with trough concentrations !38.1 mg/L.…”
Section: Future Perspectivementioning
confidence: 99%